A Reexamination of the Textual Tradition of the Hebrew Translation of Isaac Israeli's Book of Elements (Sefer ha-Yesodot) - Engel, Michael ca. 20./21. Jh. (Henoch, 2022)
The article reconstructs the textual history of the Hebrew version of Isaac Israeli’s Book of Elements. Through an analysis of varients and a comparison with the Latin translation, the author identifies two independent cases of textual revision, conducted most likely in Spain and Provence. In addition, the author identifies a version which is most likely the closest to the original Hebrew translation, contained in a group of Italian manuscripts.